Perkembangan Pola Permukiman Tradisional Berbasis Kearifan Lokal Desa Luluo Kecamatan Biluhu Kabupaten Gorontalo - Liberty Lodjo; Sulfiani Sulfiani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Traditional settlements are a reflection of the way of life, cultural values, and interactions of society with the natural environment. In the context of Luluo Village, settlement patterns are not only formed by physical factors such as topography and natural resources, but are also influenced by the local wisdom of the Gorontalo people who have a value system, customs, and cosmology-based spatial planning. The objectives of this study are: 1) To describe the traditional settlement patterns of Luluo Village, Biluhu District, Gorontalo Regency; 2) To analyze the development and changes in settlement patterns in Luluo Village; 3) To identify forms of local wisdom that play a role in the formation and preservation of settlement patterns. Method: used in this study is a qualitative descriptive method. Results: This study is 1) Traditional Settlement Patterns of Luluo Village seen from the distribution pattern of houses, building orientation, distance between houses, open spaces. 2) forms of local wisdom in traditional settlements. 3) The development of settlements in Luluo Village. 4) The impact of settlement development on socio-cultural life. Conclusion: Based on the results of this study, it can be concluded that the development of traditional settlement patterns in Luluo Village is a dynamic process influenced by environmental, social, cultural, and economic factors. Local wisdom is the main foundation in the formation and development of settlements, despite facing the challenges of modernization. Traditional settlement patterns based on local wisdom have proven capable of creating a harmonious, sustainable, and socially value-oriented residential environment.